Numerical and Experimental Study on Soil Plug Resistance of Open-Ended Pipe Pile with a Restriction Plate - Yuan Guo; Shaoyang Dong; Jiale Li; Xiong (Bill) Yu (Advances in Civil Engineering)
The end bearing capacity of open-ended pipe piles is highly dependent upon the soil plugging behavior inside the pipe wall. For large-diameter open-ended pipe piles, the arching effect due to inner soil-pile friction may be insufficient to generate a fully plugged condition, which compromises the end bearing capacity after the pile installation. Here, we propose two innovatively designed restriction plates installed inside the pipe to facilitate the soil plugging process, that is, a restriction plate with one circular hole and a restriction plate with four semisized circular holes. By use of the discrete element method, the mechanical behaviors of soil plugs in cohesionless soils with different restriction plates are analyzed. The numerical model has been validated by comparing the simulations to the results of a series of laboratory-scale experiments over different pile diameters, plug length-diameter ratios, and different types of restriction plates. It is shown that the numerical model can accurately predict the soil plug resistance and the particle-scale force transmission. Both numerical simulations and experiments validate that the arching effect is significantly enhanced by the restriction plate, especially with the four-hole restriction plate. Furthermore, the geotechnical centrifuge principle is adopted into the DEM model to study the mechanical behavior of large-diameter soil plugs. It is found that the effectiveness of restriction plate decreases as the pile diameter increases. However, even for the 2 m in diameter soil plugs, the plug resistance is increased by 252% with one-hole restriction plate and 281% with four-hole restriction plate compared to that of traditional pipe piles.